2018
DOI: 10.1186/s40560-018-0321-9
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged low-dose methylprednisolone treatment is highly effective in reducing duration of mechanical ventilation and mortality in patients with ARDS

Abstract: An updated meta-analysis incorporating nine randomized trials (n = 816) investigating low-to-moderate dose prolonged glucocorticoid treatment in acute respiratory distress syndrome (ARDS) show moderate-to-high quality evidence that glucocorticoid therapy is safe and reduces (i) time to endotracheal extubation, (ii) duration of hospitalization, and (iii) mortality (number to treat to save one life = 7), and increases the number of days free from (i) mechanical ventilation, (ii) intensive care unit stay, and (ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(99 citation statements)
references
References 36 publications
4
87
0
2
Order By: Relevance
“…One systematic review conducted an analysis of individual patient data from randomized trials, and found that, compared with the placebo group, prolonged glucocorticoid treatment improved clinical outcomes (32). A recent individual patient data meta-analysis combined four RCTs evaluating prolonged methylprednisolone therapy for ARDS and reported a significant reduction in mortality, with an increase in ventilator-free days (13 vs. 7, p < 0.001) (33).…”
Section: Discussionmentioning
confidence: 99%
“…One systematic review conducted an analysis of individual patient data from randomized trials, and found that, compared with the placebo group, prolonged glucocorticoid treatment improved clinical outcomes (32). A recent individual patient data meta-analysis combined four RCTs evaluating prolonged methylprednisolone therapy for ARDS and reported a significant reduction in mortality, with an increase in ventilator-free days (13 vs. 7, p < 0.001) (33).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that treatment with high-dose corticosteroids for a prolonged period of time could accelerate the improvement of ARDS [22]. Furthermore, methylprednisolone shortened periods of need for invasive mechanical ventilation and lowered mortality in ARDS patients [23]. However, WHO recommended that systemic corticosteroids should not be routinely administered to COVID-19 or COVID-19-related ARDS patients [20].…”
Section: Corticosteroids In Covid-19-related Ards Patientsmentioning
confidence: 99%
“…Prior studies for corticosteroids in ARDS are controversial, but perhaps low dose steroids do reduce duration of mechanical ventilation. (16,17) Current recommendations advise against corticosteroids for in uenza pneumonia, but in critically ill patients on vasopressors, there is a contrary recommendation to suggest steroids for vasopressor refractory shock. (18,19) Vitamin C has been already used in COVID 19 patients requiring mechanical ventilation and studies are underway looking at the combination of Vitamin C and corticosteroids in COVID-19.…”
Section: Discussionmentioning
confidence: 99%